Diseño de plan de mantenimiento de banco didáctico de transmisión de potencia mecánica (2020)
The design of the maintenance plan for the mechanical power bank is based on the continuous improvement that the UAN must maintain towards its assets, which are very useful for the theoretical-practical learning of its students. The design of this maintenance plan is built to maintain internal control of the maintenance of the transmission system as a team, focusing on the failures that it has presented and, in turn, the future ones that can be prevented thanks to the programmed activities, extending its useful life. and being of great benefit to the community of the institution.